Spatiotemporal Impact of Urban Impervious Surface on Land Surface Temperature in Shanghai, China. Issue 6 (1st November 2016) - Nie, Qin; Man, Wang; Li, Zongmei; Huang, Yutong
Abstract: Numerous studies have previously demonstrated the positive correlation between urban impervious surfaces (UIS) and land surface temperature (LST) from single or multitemporal images, but little attention has been paid to the basic mechanisms governing the process of UIS–LST relationship change. This study investigates how the UIS–LST relationship evolves with urbanization and how the spatiotemporal change in UIS quantitatively affects LST in Shanghai, China. UIS change trajectory is introduced to determine the spatiotemporal UIS change, and indices of LST deviation degree and contribution ratio are applied to determine the quantitative effect of spatiotemporal UIS change on LST. The results show a positive UIS–LST correlation during 1997 to 2010. The changes in the standard deviation of mean LST for corresponding UIS types suggest that the mean LST of all UIS types experienced broad variability in 1997, with these variations decreasing during 1997 to 2007 and then increasing in 2010. The trajectories transforming into UIS7 represent the main UIS change pattern in the study area. The LST change of these trajectories is the smallest among all change trajectories, but these trajectories dominate the LST change of the entire study area due to the vast region covered by these trajectories.